2003
DOI: 10.1182/blood-2003-05-1675
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic    T-cell lymphoma is a rare clinicopathologic entity with poor outcome: report on a series of 21 patients

Abstract: We report on the characteristics of 21 patients with hepatosplenic ␥␦ T-cell lymphoma (HS␥␦TCL), an entity recognized since 1994 in the Revised European American Lymphoma (REAL) classification. Median age was 34 years. Patients had splenomegaly (n ‫؍‬ 21), hepatomegaly (n ‫؍‬ 15), and thrombocytopenia (n ‫؍‬ 20). Histopathologic findings were homogeneous and showed the presence of medium-sized lymphoma cells within the sinusoids of splenic red pulp, liver, and bone marrow. Marrow involvement was usually mild b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
409
2
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 408 publications
(426 citation statements)
references
References 76 publications
7
409
2
8
Order By: Relevance
“…Because γδ T cells have preferential homing to the sinusoidal areas, marked sinusoidal infiltration is noted in both the liver and spleen [104]. EBV has been reported to be not associated with hepatosplenic T-cell lymphoma in most studies [103,105,106]; however, few studies have reported the detection of EBV genome by Southern blot and in situ hybridization in patients with the disease [85,107]. A hypothesized possible role for EBV in the pathogenesis of the disease can be debated because of the inconsistent EBV detection, although one may argue that it may play a role via chronic antigen exposure [85].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 99%
“…Because γδ T cells have preferential homing to the sinusoidal areas, marked sinusoidal infiltration is noted in both the liver and spleen [104]. EBV has been reported to be not associated with hepatosplenic T-cell lymphoma in most studies [103,105,106]; however, few studies have reported the detection of EBV genome by Southern blot and in situ hybridization in patients with the disease [85,107]. A hypothesized possible role for EBV in the pathogenesis of the disease can be debated because of the inconsistent EBV detection, although one may argue that it may play a role via chronic antigen exposure [85].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 99%
“…Chronic antigenic stimulation from transplanted allograft and the associated expansion of CD3 1 CD4 2 CD8 2 TCRab 2 T-cells may contribute to the pathogenesis [18]. This hypothesis is supported by reports of HSTL arising in other conditions that are also associated with chronic antigenic stimulation and gd T-cell expansion [3].…”
Section: Discussion and Literature Reviewmentioning
confidence: 79%
“…Bone marrow involvement was universal [3]; however, in 6 of 12 cases, the diagnosis was not made on initial bone marrow examination performed to investigate cytopenia. The characteristic sinusoidal lymphoid infiltrate is often subtle and difficult to recognize on routine H&E stain; diagnostic yield can be enhanced by immunohistochemical staining [3,17]. In a large single institution series, the diagnosis of HSTL was initially missed in a third of marrow samples; all were retrospectively found to be involved [3].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations